Prevalence of common mental disorders among medical students in China: a systematic review and meta-analysis - Wang, Jinxingyi; Liu, Min; Bai, Jian; Chen, Yuhan; Xia, Jie; Liang, Baolin; Wei, Ruixuan; Lin, Jiayin; Wu, Jiajun; Xiong, Peng (Frontiers in Public Health, 2023)
Background. The prevalence of mental distress is common for medical students in China due to factors such as the long duration of schooling, stressful doctor-patient relationship, numerous patient population, and limited medical resources. However, previous studies have failed to provide comprehensive prevalence of these mental disorders in this population. This metaanalysis aimed to estimate the prevalence of common mental disorders (CMDs), including depression, anxiety, and suicide behaviours, among medical students in China.Methods. We conducted a systematic search for empirical studies on the prevalence of depression, anxiety, suicide attempt, suicide ideation, and suicide plans in Chinese medical students published from January 2000 to December 2020. All data were collected pre-COVID-19. The prevalence and heterogeneity estimation was computed by using a random-effects model and univariate meta-regression analyses.Results. A total of 197 studies conducted in 23 provinces in China were included for the final meta-analysis. The prevalence data of depression, anxiety, suicide attempt, suicide ideation, and suicide plans were extracted from 129, 80, 21, 53, and 14 studies, respectively. The overall pooled crude prevalence for depression was 29% (38 309/132 343; 95% confidence interval [CI]: 26-32%); anxiety, 18% (19 479/105 397; 95% CI: 15-20%); suicide ideation, 13% (15 546/119 069; 95% CI: 11-15%); suicide attempt, 3% (1730/69 786; 95% CI: 1-4%); and suicide plans, 4% (1188/27 025; 95% CI: 3-6%).Conclusions. This meta-analysis demonstrated the high prevalence of CMDs amongst Chinese medical students. Further research is needed to identify targeted strategies to improve the mental health in this population.